2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347240
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial population dynamics of stem cell lineage in tissue growth

Abstract: Understanding the dynamics of cell population allows insight into the control mechanism of the growth and development of mammalian tissues. It is well known that the proliferation and differentiation among stem cells (SCs), intermediate progenitor cells (IPCs), and fully differentiated cells (FDCs) are under different activation and inhibition controls. Secreted factors in negative feedback loops have already been identified as major elements in regulating the numbers of different cell types and in maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We explore the effects of inhibition range of secreted factor to stem cell growth, as well as the effects of symmetric vs asymmetric cell divisions of stem cells. Additional detailed study of other aspects of tissue size control can be found in [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…We explore the effects of inhibition range of secreted factor to stem cell growth, as well as the effects of symmetric vs asymmetric cell divisions of stem cells. Additional detailed study of other aspects of tissue size control can be found in [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…A novel temporal-spatial cell population dynamics model has been developed to realistically model wound healing by combining a realistic cell growth model [13] with the population dynamics of stem cell niche and lineages [14]. The geometries and forces for cell growth and divisions are incorporated in the cell growth model, and the growth rates and division types after receiving inhibitions from surrounding differentiated cells are modeled individually in negative feedback controls.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2012) presented a partial differential equation (PDE)model of Wnt, BMP and their feedback regulation on a colon crypt cell lineage, which included separate compartments for stem/transit amplifying cells and terminally differentiated cells, and studied mechanisms for intestinal crypt formation. Cao et al (2012) modeled stem, progenitor and differentiated cells as geometric objects and showed that negative feedback on cell division and self-renewal contributes to homeostatic size control in tissue development. Smallbone and Corfe (2014) developed data-driven models that capture feedback control between stem and differentiated cells.…”
Section: Introductionmentioning
confidence: 99%